Potoczna wiedza o cukrzycy: porównanie osób posiadających i nieposiadających chorego na cukrzycę w rodzinie - Olchowska-Kotala, Agnieszka (Acta Universitatis Lodziensis. Folia Psychologica, 2012)
The aim of the study was to examine the perception of diabetes and the knowledge about this disease. Participants were divided into two groups: the first one consisted of family members of diabetic patients (56 individuals; M age = 54) whereas the second one comprised those who had no family experiences with diabetes (104 individuals; M age = 55). In order to examine the perception of diabetes modified version of IPQ-R (The Revised Illness Perception Questionnaire), enabling examination of healthy individuals was applied. Additionally, participants were to decide whether certain given information on diabetes was true or false. Participants in both groups considered diabetes as a serious chronic disease which can be successfully treated and the course of which is largely dependent on a patient’s behaviour. In both groups there were false assumptions regarding the causes of the disease and opinions discordant with medical knowledge. It would be advisable to organize educational campaigns and screening programmes for the family members. As a result, family members would be able to provide better support for the patient and could also recognize dysfunctions of their own organism early enough.